2016
DOI: 10.21082/ijas.v10n2.2009.p80-87
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Roti Quality of Sorghum Genotypes

Abstract: Sorghum grains are mostly used for the roti preparation. The M 35-1 (Maldhandi) a sorghum cultivar is known for its good quality of roti due to having pearly white grain color, its flour having higher water holding capacity, and good organoleptic taste. However, this cultivar is low yielder. To evolve sorghum high yielding genotype coupled with this good roti qualities, systematic breeding program was planned and executed to overcome this problem. Twenty local land races, 92 genotypes, and seven improved culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…Johann et al (2012), reported brown and white rice to have range of 1.60 to 4.74mg/kg and 0.78 to 2.71 mg/kg with mean of 2.96mg/kg and 1.65mg/kg of Copper. Also Chavan et al, (2009), reported range of 0.53 to 1.08mg/kg with mean of 0.86mg/kg copper in some varieties of sorghum. The copper content of coarse grains obtained in this study was higher than the above reports.…”
Section: Coppermentioning
confidence: 96%
“…Johann et al (2012), reported brown and white rice to have range of 1.60 to 4.74mg/kg and 0.78 to 2.71 mg/kg with mean of 2.96mg/kg and 1.65mg/kg of Copper. Also Chavan et al, (2009), reported range of 0.53 to 1.08mg/kg with mean of 0.86mg/kg copper in some varieties of sorghum. The copper content of coarse grains obtained in this study was higher than the above reports.…”
Section: Coppermentioning
confidence: 96%
“…Some inbred and hybrid lines of sorghum in Kansas (Hicks et al, 2002) and African sorghum lines (Aba et al, 2005) had a similar crude protein range of 10.3 to 16.5% and 10 to 16.45%, respectively. Genetic variability of sorghum accessions was reported to contribute to the variation in crude protein content of the accessions evaluated (Chavan et al, 2009;Ng'uni et al, 2012). In this study, the growing environment had an affect on accumulation of crude protein in some of the sorghum lines evaluated (Table 1).…”
Section: Crude Proteinsmentioning
confidence: 99%
“…Sorghum nutritional composition is like other major cereals, is a good source of energy, macronutrients and micronutrients, also it is rich in polyunsaturated fatty acids, these are present mainly in the germ of the grain. Therefore, its quality, availability, storage, use and consumption contribute to food security and nutrition wherever required, and it is also considered an adequate food for people with pathologies such as diabetes and obesity, due to its high vitamin, mineral and fiber contents (Chavan et al, 2016;Hadebe et al, 2017;Mehmood et al, 2008).…”
Section: Introductionmentioning
confidence: 99%